miR-19b-3p/PKNOX1 Regulates Viral Myocarditis by Regulating Macrophage Polarization - Jiahui, Chen; Jiadai, Zheng; Nan, Zheng; Rui, Zhou; Lipin, Huang; Jian, He; Wenzong, Zhu; Riyuan, Zhang (Frontiers in Genetics, 2022)
The purpose of this study is to study the role and mechanism of miR-19b-3p in regulating myocardial inflammation and injury of (VM) in viral myocarditis induced by coxsackievirus B3 (CVB3). Methods The mouse model of CVB3 infection was established and treated with miR-19b-3p mimic. the survival rate of mice was recorded and the cardiac function was detected. The degree of myocardial inflammatory infiltration and injury was detected by immunohistochemical and biochemical analysis. PCR was used to detect the expression of miR-19b-3p and PKNOX1 in heart tissue and cardiac infiltrating macrophages. Mouse bone marrow-derived macrophages were isolated and the differentiation of macrophages after different transfection was detected. Finally, the binding of miR-19b-3p and PKNOX1 was verified by double luciferase reporter gene. Results The expression of miR-19b-3p in heart tissue and infiltrating macrophages of CVB3 infected mice was significantly down-regulated while the expression of PKNOX1 was increased. Up-regulation of miR-19b-3p in vivo had a protective effect on CVB3-induced myocardial injury in mice, such as weight gain, prolonged survival time, increase of left ventricular ejection fraction and left ventricular short axis shortening, and reduction of inflammation. The levels of creatine kinase isoenzyme (CK-MB), lactate dehydrogenase (LDH) and aspartate aminotransferase (AST) decreased, while the levels of interferon-γ, interleukin-6 (IL-6) and interleukin-10 (IL-10) increased. At the same time, they significantly inhibited the expression of M1 markers (inducible nitric oxide synthase, tumor necrosis factor α) and promoted the expression of M2 markers (arginase-1, FIZZ-1). The ratio of M2/M1 cells was up-regulated and the mechanism analysis showed that miR-19b-3p directly targeted to inhibit the expression of PKNOX1, thus regulating the differentiation of macrophages. Conclusion MiR-19b-3p can regulate the polarization of macrophages by targeting PKNOX1, which has a protective effect on CVB3-induced inflammation and myocardial injury.